2006
DOI: 10.1111/j.1530-0277.2006.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

A 3‐Year Study of Addiction Mutual‐help Group Participation Following Intensive Outpatient Treatment

Abstract: Use of mutual-help groups following intensive outpatient SUD treatment appears to be beneficial for many different types of patients and even modest levels of participation may be helpful. Future emphasis should be placed on ways to engage individuals with these cost-effective resources over time and to gather and disseminate evidence regarding additional mutual-help organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 79 publications
7
84
3
Order By: Relevance
“…GAATOR = General Alcoholics Anonymous Tools of Recovery; SOS = Service to Others in Sobriety; RBB = Religious Beliefs and Behaviors; PPTS = percentage positive toxicology screens; A-OCDS = Adolescent-Obsessive Compulsive Drinking Scale; CGAS = Children's Global Assessment Scale; NPI = Narcissistic Personality Inventory. nors et al, 2001;Kelly et al, 2006;Winzelberg and Humphreys, 1999), it is unclear how religiosity/spirituality may infl uence adolescent 12-step participation during treatment and outcomes.…”
Section: Infl Uence Of Religiosity On 12-step Participation and Treatmentioning
confidence: 99%
“…GAATOR = General Alcoholics Anonymous Tools of Recovery; SOS = Service to Others in Sobriety; RBB = Religious Beliefs and Behaviors; PPTS = percentage positive toxicology screens; A-OCDS = Adolescent-Obsessive Compulsive Drinking Scale; CGAS = Children's Global Assessment Scale; NPI = Narcissistic Personality Inventory. nors et al, 2001;Kelly et al, 2006;Winzelberg and Humphreys, 1999), it is unclear how religiosity/spirituality may infl uence adolescent 12-step participation during treatment and outcomes.…”
Section: Infl Uence Of Religiosity On 12-step Participation and Treatmentioning
confidence: 99%
“…Many mutual aid groups follow some version of the 12-step model of recovery originally developed by the founders of Alcoholics Anonymous (AA) (Alcoholics Anonymous, 1939/2001/1952. Growing evidence indicates that 12-step groups are useful in maintaining abstinence from "substances of abuse" (e.g., Devine et al, 1997;Humphreys et al, 1994;Timko et al, 2000;Timko et al, 2006;Thurstin et al, 1987;Tonigan et al, 2002;;Humphreys and Moos, 2007;Kaskutas et al, 2005;Kelly et al, 2006;McCrady & Miller, 1993), especially for those who attend regularly or become affiliated (e.g., Fiorentine et al, 1999;Kingree, 1995;McKay et al, 1994;Montgomery et al, 1991;Watson et al, 1997). For example, Moos et al, (1999) found that increased attendance in 12-step groups was associated with a higher proportion of abstinence from drugs and alcohol, less severe distress and psychiatric symptoms, and a higher likelihood of being employed at one-year follow-up.…”
Section: Effectiveness Of Mutual Aidmentioning
confidence: 99%
“…Studies on 12-step participation traditionally were limited to relatively short-term follow-up periods that are inadequate to study remission from chronic disorders (typically under two years); several recent reports have extended the timeframe significantly including a 16-year follow-up study of initially untreated alcohol-dependent persons showing that 12-step participation in the first year of the study predicted better substance use outcomes at 16 years ; also see Kaskutas, Ammon, Delucchi, Room, Bond, and Weisner, 2005;Kelly, Stout, Zywiak, and Schneider, 2006). As with formal treatment, longer duration and higher level of 12-step meeting attendance are associated with better outcomes (e.g., Fiorentine, 1999;Moos, Schaefer and Moos et al, 2001;.…”
Section: Research On 12-step Participationmentioning
confidence: 99%
“…In several studies, 12-step meeting attendance was the best single predictor of positive outcome following treatment for substance use disorders (Morgensten et al, 2003), a factor that rises in tandem with addiction severity (Tonigan et al, 1995). Further, the probability of stable remission increases with the number of meetings attended early on (Hoffmann, Harrison, Belille, 1983;Pisani, Fawcett, Clark, and McGuire, 1993;Humphreys, Moos, and Cohen, 1997).Studies on 12-step participation traditionally were limited to relatively short-term follow-up periods that are inadequate to study remission from chronic disorders (typically under two years); several recent reports have extended the timeframe significantly including a 16-year follow-up study of initially untreated alcohol-dependent persons showing that 12-step participation in the first year of the study predicted better substance use outcomes at 16 years ; also see Kaskutas, Ammon, Delucchi, Room, Bond, and Weisner, 2005;Kelly, Stout, Zywiak, and Schneider, 2006). As with formal treatment, longer duration and higher level of 12-step meeting attendance are associated with better outcomes (e.g., Fiorentine, 1999;Moos, Schaefer and Moos et al, 2001;.…”
mentioning
confidence: 99%